2023
DOI: 10.1371/journal.pone.0288322
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with depression, anxiety, and stress among people with disabilities during COVID-19 pandemic in Bangladesh: A cross-sectional study

Abstract: Background The COVID-19 pandemic has had a profound impact on the mental health of individuals across various populations. People with disabilities (PWDs) are particularly vulnerable to these effects, yet there is a lack of studies investigating the mental health of PWDs in Bangladesh. This study aims to investigate the prevalence of and factors associated with depression, anxiety, and stress among PWDs during the COVID-19 pandemic in Bangladesh. Methods Data was collected through interviews with 391 PWDs be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This study from the United States used a randomized trial to assess the relationship between changes in functional disability and suicidal ideation in older adults following depression psychotherapy. A cross-sectional study from Bangladesh reported by Roy et al ( 62 ) found a 65.7% prevalence rate of depression among general disabled people. Another study, ( 48 ), measured depression in general disabled participants using the patient health questionnaire (PHQ-9) and discovered that 61% of them were depressed.…”
Section: Resultsmentioning
confidence: 97%
“…This study from the United States used a randomized trial to assess the relationship between changes in functional disability and suicidal ideation in older adults following depression psychotherapy. A cross-sectional study from Bangladesh reported by Roy et al ( 62 ) found a 65.7% prevalence rate of depression among general disabled people. Another study, ( 48 ), measured depression in general disabled participants using the patient health questionnaire (PHQ-9) and discovered that 61% of them were depressed.…”
Section: Resultsmentioning
confidence: 97%
“…These findings have suggested that depression and anxiety symptomatology must be explored as a potential target for protective interventions against persistent symptomatology due to COVID-19 infection [81]. In another cross-sectional survey, the incidence of depression, anxiety, and stress was shown to be extremely high, reaching 65.7%, 78.5%, and 61.4% of the study population, respectively [82]. Diverse factors have been shown to be related to mental health problems in people with disabilities, such as gender (male), marital state (being married), decreased educational status, comorbid medical diseases, low sleep quality, living in rural regions, hearing disability, disability onset later in life, and testing positive for COVID-19 [82].…”
Section: Discussionmentioning
confidence: 94%
“…Drawing upon earlier global findings on post-COVID-19 psychological sequelae, s we hypothesised that a significant proportion of individuals who recovered from COVID-19 in Dhaka city would manifest symptoms of depression and anxiety. In Bangladesh, there have been numerous studies to investigate the mental health status of people during the coronvirus outbreak ( 26 29 ). To date, little research has been conducted in the country to evaluate psychological outcomes in survivors of COVID-19 ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%